A global taxonomic review and analysis of the development of BIM research between 2006 and 2017. Issue 3 (7th July 2019) - Saka, Abdullahi Babatunde; Chan, Daniel W.M.
Abstract : Purpose: This paper aims to review the status of development of building information modelling (BIM), its trends and themes across the six continents of the world. Design/methodology/approach: A total of 914 journal articles sought from the search engine of Web of Science (WOS) based on the country/region option of the WOS to group them into continents. A best-fit approach was then applied in selecting the suitable software programmes for the scientometric analysis and comparisons and deductions were made. Findings: The findings revealed that there are differences in the development of BIM across the six continents of the world. South America and Africa are lagging in the BIM research and Australia and Asia are growing, whilst Europe and North America are ahead. In addition, there exist differences in the research themes and trends in these continents as against the single view presented in extant studies. Originality/value: This study introduced a new approach to carry out a comparative and taxonomic review and has provided both academic researchers and industrial practitioners with a clear status of development of BIM research and the trend across the six continents of the world.